Effects Of Heating Rates And SBE Loading On Sintered Properties Of Spent Bleach Earth/Recycled Glass Composite - Nik Mohd Salleh, Nik Muhammad Farid; Shamsudin, Zurina; Mohamad Juoi, Jariah; Mustafa, Zaleha (Universiti Malaysia Pahang, 2017)
The purpose of this study is to investigate the influence of different heating rates on the properties of glass ceramic composite (GCC) at different spent bleach earth (SBE) loadings. GCC was prepared using SBE and recycled soda lime silicate (SLS) glass. The particle size of SLS glass was approximately <45μm. The GCC was formed by uniaxial dry pressing at weight fractions of SBE loading of 40 wt. %, 45 wt. %, and 55 wt. %. The GCC was then sintered at different heating rates of 2 ºC/min, 4 ˚C/min, 6 ºC/min and 8 ˚C/min at 700 ºC of sintering temperature. The GCC specimens were analysed in terms of their physical properties, while crystalline phase and microstructure were characterized using X-Ray diffraction and scanning electron microscope (SEM), respectively. The results from X-Ray diffraction pattern showed that quartz and wollastonite phases were formed with no major changes on the phases as the heating rate increased. The results indicate that the variation of heating with 2 ºC/min interval does not give a remarkable result of physical properties on GCC. High loading of SBE sintered at 2 ºC/min of heating rate produced low water absorption, density and porosity. SEM analysis showed that the physical properties and crystalline phases were correlated to the SBE loading and changes in the heating rate. The study concluded with the prospect of continuing the work of optimisation on schedule heat treatment at sintering temperature regimes.